Differential lipidome remodeling during postharvest of peach varieties with different susceptibility to chilling injury - Bustamante, Claudia Anabel; Brotman, Yavid; Monti, Laura L.; Gabilondo, Julieta; Budde, Claudio Olaf; Lara, María Valeria; Fernie, Alisdair R.; Drincovich, María Fabiana (2018)
Peaches ripen and deteriorate rapidly at room temperature. Therefore, refrigeration is used to slow these processes and to extend fruit market life; however, many fruits develop chilling injury (CI) during storage at low temperature. Given that cell membranes are likely sites of the primary effects of chilling, the lipidome of six peach varieties with different susceptibility to CI was analyzed under different postharvest conditions. By using liquid chromatography coupled to mass spectrometry (LC–MS), 59 lipid species were detected, including diacyl- and triacylglycerides. The decreases in fruit firmness during postharvest ripening were accompanied by changes in the relative amount of several plastidic glycerolipid and triacylglyceride species, which may indicate their use as fuels prior to fruit senescence. In addition, levels of galactolipids were also modified in fruits stored at 0∘C for short and long periods, reflecting the stabilization of plastidic membranes at low temperature. When comparing susceptible and resistant varieties, the relative abundance of certain species of the lipid classes phosphatidylethanolamine, phosphatidylcholine and digalactosyldiacylglycerol correlated with the tolerance to CI, reflecting the importance of the plasma membrane in the development of CI symptoms and allowing the identification of possible lipid markers for chilling resistance. Finally, transcriptional analysis of genes involved in galactolipid metabolism revealed candidate genes responsible for the observed changes after cold exposure. When taken together, our results highlight the importance of plastids in the postharvest physiology of fruits and provide evidence that lipid composition and metabolism have a profound influence on the cold response.